Giant omphalocele: current perspectives - Mack AJ; Rogdo B (Dove Medical Press, 2016)
Alexander Josef Mack,1 Bjarte Rogdo2 1Department of Pediatric Surgery, 2Pediatric and Neonatal Intensive Care Unit, Children’s Hospital of Eastern Switzerland, St Gallen, Switzerland Abstract: Giant omphalocele (GO) is a congenital ventral abdominal wall defect characterized by a large opening with herniated abdominal organs, including liver, loss of abdominal cavity volume, and other associated congenital anomalies. Treatment of patients with GO represents a major challenge for involved caregivers. Despite significant improvements in neonatal intensive and surgical care over the last decades, the condition is still associated with high mortality rates and a high risk of severe morbidity in survivors. The principles of the earliest attempts to treat GO surgically and conservatively are still easily recognized in the main approaches used today. In this review, we discuss the more recent developments in the treatment of GO, including perioperative management and associated morbidities of the condition. Keywords: giant omphalocele, abdominal wall closure, staged repair, delayed repair